PENGARUH SELF ESTEEM TERHADAP TINGKAT STRES MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS LAMBUNG MANGKURAT TAHUN 2023 - Gitarasy, Anindya Syifa; Khairiah, Siti; Istiana, Istiana (Homeostasis, 2024)
Abstract: Stress is a situation where the existing demands are beyond the individual's response capacity to said demands, causing negative physical and psychological consequences. Medical students in particular often reported chronic stress events experience. Self-esteem is belief in one's ability to think and to overcome all life's challenges. Students with high self-esteem appear to have lower levels of stress than those who have low self-esteem and thus possessed higher levels of stress. This research is aimed to analyse the impact of self-esteem on stress levels of students at the Medicine Faculty of Universitas Lambung Mangkurat in 2023. The analytical observational method with a cross-sectional approach research design is the method used for this research. The number of subjects taken in this research was 67 out of 154 students. The data analyzed was primary data that had been collected from the respondents of the Rosenberg Self-Esteem Scale (RSES) and Perceived Stress Scale (PSS-10) questionnaires who met the inclusion and exclusion criterias. From the data collected through the RSES questionnaire, the results showed that low self-esteem was 13.4%, moderate self-esteem was 65.7%, and high self-esteem was 20.9%. Meanwhile, from the PSS-10 questionnaire data, the light stress level was 37.3%, the moderate stress level was 55.2%, and the severe stress level was 7.5%. The results of statistical tests using the ordinal regression test obtained a value of p = 0.681, which means that there was no significant impact between self-esteem and stress levels in students at the Faculty Medicine of Universitas Lambung Mangkurat in 2023. Keywords: self-esteem, stress level, medical students. Abstrak: Stres adalah situasi dimana tuntutan yang ada melebihi kapasitas respon individu terhadap tuntutan tersebut dan menyebabkan konsekuensi fisik dan psikologis yang negatif. Mahasiswa program sarjana kedokteran secara khusus, dilaporkan sering mengalami kejadian stres yang kronis. Self-esteem adalah keyakinan akan kemampuan diri untuk menalarkan dan mengatasi segala rintangan hidup. Siswa dengan self-esteem yang tinggi tampak menunjukkan tingkat stres yang lebih rendah dari mereka yang memiliki self-esteem rendah dan kemudian memiliki stres yang tinggi. Penelitian ini ditujukan untuk menganalisis adanya pengaruh self-esteem terhadap tingkat stres mahasiswa Fakultas Kedokteran Universitas Lambung Mangkurat tahun 2023. Metode observasional analitik dengan desain pendekatan cross-sectional merupakan pilihan metode yang digunakan untuk penelitian ini. Jumlah subjek yang diambil dalam penelitian ini berjumlah 67 orang dari total 154 orang mahasiswa. Data yang dianalisis merupakan data primer yang telah dikolektifkan dari para responden kuesioner Rosenberg Self-Esteem Scale (RSES) dan Perceived Stress Scale (PSS-10) yang memenuhi kriteria inklusi dan eksklusi. Dari data yang dikumpulkan melalui kuesioner RSES didapatkan hasil self-esteem rendah 13,4%, self-esteem sedang 65,7%, dan self-esteem tinggi 20,9%. Sedangkan dari data kuesioner PSS-10 didapatkan hasil tingkat stres ringan 37,3%, tingkat stres sedang 55,2%, dan tingkat stres berat 7,5%. Hasil uji statistik menggunakan uji regresi ordinal didapatkan nilai p = 0.681 yang mana berarti bahwa tidak ditemukan pengaruh yang signifikan antara self-esteem terhadap tingkat stres mahasiswa Fakultas Kedokteran Universitas Lambung Mangkurat tahun 2023. Kata-kata kunci: self-esteem, tingkat stres, mahasiswa Fakultas Kedokteran.